Fantasy Pitching - Robert W. Faff; Searat Ali; Muhammad Atif; Matt Brenner; Hasibul Chowdhury; Leelyn Crudas; Alison Joubet; Ihtisham Malik; Lin Mi; Vinu Nagar; Tim Pullen; Manuel Siegrist; et al. (Journal of Accounting and Management Information Systems (JAMIS), 2017)
This paper outlines a fantasy research pitch exercise conducted in a PhD course at the University of Queensland. Using Faff's (2015, 2017) pitching research template, students attending the course were asked to engage in a group exercise to pitch a "fantasy" research topic. While the final exercise was completed in a 90-minute timeframe (60 minutes of brainstorming, followed by 30 minutes of reporting back to the full group), the cohort had already been exposed to 5 x 90 minute sessions of related material over the weekend PhD module. Three groups of five were formed and they pitched three "fun" (or nonsense) topics: (a) Teenage Mutant Ninja Turtles: Impact on Society; (b) Wipe-a-Baby; (c) Quality of Dairy Products: The Happiness of the Cow Does Matter.
Keywords: G00; M00; B40; A20; B00; C00; D00; E00; F00; H00; I00; J00; L00; Q00; R00; Z00; 650; Pitching Research; Fantasy Pitching; PhD Student Exercise; Research Group-work Exercise